PENGARUH MEDIA MICROSOFT TEAM TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN PAI - Latifah Hanum; Acep Mulyadi (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
The definition of the issue of this examination is whether there is an impact between the Microsoft Team media on students' interest in learning in Islamic Religious Education Class X at SMAN 13 Bekasi City. This study aims to determine the influence of Microsoft Team media on student interest in learning Islamic Religious Education Class X at SMAN 13 Bekasi City. Media is whatever can be utilized to communicate messages from the shipper to the beneficiary and invigorate understudies' considerations, sentiments, interests, and considerations so that the instructing and learning process happens. In this study, the media in question is Microsoft Team. Meanwhile, interest in education is a form of activity that encourages someone to carry out a series of mental and physical activities to obtain a change in behavior as a result of individual experiences in interactions in their environment involving cognitive, affective, and psychomotor. The existence of good media that supports learning will achieve teaching and learning objectives. The research method used in this research is the Quasi Experiment method, with the Nonequivalent Control Group design, a quasi-experimental or quasi-experimental research method. The experimental class uses Microsoft Team media, and the control class does not use Microsoft Team media. The instrument in this study was a questionnaire (questionnaire) in the form of Pre-Treatment and Post-Treatment documentation. The sample used in this study amounted to 52 students. There were 26 students for the experimental and 26 for the control classes. The results of this study aimed to determine the effect of data using the